An integrated knowledge-based system for mechanical design (VOL 1) - Leong, Kar Tshon. (2009)
A computational model for solving shafting system design problems has been developed. The model, which consists of a Hierarchy of Integrated Teams of Specialists, is based on a strategy of design problem subdivision, distributed problem solving and team-work. Each team in the hierarchy is made up of a number of specialists working in a cooperative and consultative environment under the coordination of a team manager. Specialists are represented by terminating nodes in the hierarchy and team managers are represented by non-terminating nodes.